Molecular pathology of cancer - Doimi-García, Franco (2020)
The pathology has evolved together with scientific and technological advances, perhaps being the oncologydiscipline where these advances have been incorporated more quickly into daily practice. Molecular pathology stems from advances in the understanding of the human genome and the subsequent description of cancer genomes, as well as from the rapid simplification and cheapening of molecular techniques. Molecular pathology offers not only a more comprehensive description of the characteristics of cancer, but also provides the treating physician with a range of cancer weaknesses that are therapeutic targets.